If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1) = -4x + 29 Reorder the terms: (-1 + x) = -4x + 29 Remove parenthesis around (-1 + x) -1 + x = -4x + 29 Reorder the terms: -1 + x = 29 + -4x Solving -1 + x = 29 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -1 + x + 4x = 29 + -4x + 4x Combine like terms: x + 4x = 5x -1 + 5x = 29 + -4x + 4x Combine like terms: -4x + 4x = 0 -1 + 5x = 29 + 0 -1 + 5x = 29 Add '1' to each side of the equation. -1 + 1 + 5x = 29 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 29 + 1 5x = 29 + 1 Combine like terms: 29 + 1 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 3x+36=10x-41 | | -2*2+((-1)3-3)2= | | 7.083333333=x^2-3x+6.75 | | 7.5(x-4)=-0.5x+34 | | x^2-(m+3)x+11=0 | | 14-4(3x+1)-8+2x-2= | | 8*14*11= | | 6x+59=12x+11 | | 3x^2-9x+20.25=21.25 | | q+14=8q+56 | | (2x+3)(x-1)=18 | | q+14=8q+8*7 | | x+12+8x=30 | | 7n+39=11n-13 | | u+4=4u-8 | | (2x+3)(x+1)=18 | | c+2c-5-5c=7 | | 3(2m-3)=8(m+1) | | x^3+5x^2+7x+35= | | 1.2(4x-3.2)=2 | | 2x-4(x+2)=x(2x-1) | | (7x+3)=6 | | 6C(12)=48 | | (7x+3)= | | (4x-10x)-40+3=2(x-1) | | 5z-4z=48 | | 1x=2x-7 | | 2x-37=24 | | 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 |